Analisis Dampak Pengumuman Merger dan Akuisisi Terhadap Abnormal Return Saham Pada Perusahaan Akuisitor yang Terdaftar di BEI Tahun 2013-2015 - Lusia As’ari; Mohammad Amin; Muhammad Cholid Mawardi (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
AbstractEntering the era of free trade and globalization, industry competition isgetting tougher in Indonesia. Therefore, companies need to develop a strategy inorder to maintain its extensions in the world of competition. This study focuses onexternal growth strategy is to conduct mergers and acquisitions. Mergers andacquisitions are a form of business combination of interest by the companies inIndonesia. This research is a study of events which aims to show how the stockmarket reaction to the announcement of mergers and acquisitions by usingindicators of abnormal return.The population in this study is the companies registered and listed inIndonesia Stock Exchange (BEI). The sample used in this study is the companiesannounced a merger and acquisition information from 2013 to 2015 period.Based on the criteria, it is acquired 26 companies sampled in this study.Hypothesis testing is paired samples t-test. Based on the results of data analysiscan be concluded that there is no difference in abnormal returns before and afterthe announcement of mergers and acquisitions as indicated by the t-test value of0,939 is more than 0,05 (> 0.05). Then H0 accepted, H1 rejected.Key words: Merger and Acquisition, Abnormal Return